In silico study of COX-2 on indomethacin and diclofenac as nonsteroidal anti-inflammatory drugs (NSAIDs) - Na'imah, Janatun (Farmasains : Jurnal Farmasi dan Ilmu Kesehatan, 2019)
Cyclooxygenase is an enzyme that plays a role in the formation of prostaglandins, which can cause inflammation and pain when overexpressed. This study aims to determine the interaction between COX-2 macromolecules (receptors) with their ligands, namely indomethacin and diclofenac in silico using the Molecular Docking method. The COX-2 receptor was downloaded in the form of a 3D structure from the RCSB GDP with code 5F19. Diclofenac Ligand and Indomethacin were downloaded in the form of a 3D structure from the RCSB GDP with 4ZBQ code and 4IK7 code. The results showed that the interaction between COX-2 and indomethacin was the interaction of hydrogen, which linked indomethacin with amino acid Leu531 and steric interactions between indomethacin and amino acids Trp387, Tyr385, Tyr355, Leu352, and Val523. The interaction of [COX-2 – Indomethacin] produces a value of ∆G of -103.136 kcal/mol, and the value of RMSD is 1.244 Å. Whereas, the interaction that occurs in COX-2 with diclofenac is the steric interaction that happens between diclofenac with amino acids Leu390, Trp387, Gln203, His388, His207, and Thr206. The interaction parameter between [COX-2-Diclofenac] obtained ∆G value of -7.843 kcal/mol and an RMSD value of 2.07851 Å.